Penerapan Model Treffinger Berbasis Lingkungan dalam Pembelajaran Seni Tari untuk Meningkatkan Karakter Kreatif Siswa - Vitria Mega Utami; Trianti Nugraheni (Gondang: Jurnal Seni dan Budaya, 2019)
The purpose of this research was to develop the students' creative characters in fluency, flexibility, originality, elaboration and redefinition through dance learning using Treffinger-surrounding based- method. The subject of the research was students of XI social 4 of SMAN 8 CRB. In the process, the surrounding was used as the stimulus of the dance creation as the real product that shown the character development of students' creativity. The learning method that was being implemented in four meetings was based on the steps of Treffinger method that is basic tool, practice woth process, and working with real problem.the method that was used in this research was exprimental research with the paradigm of quantitative. The result of this research proved that there was the increase of students' score by comparing the pre-test and post-test results. The average of pretest was 64 and after the treatment the posttest result was 82.  Beside that, the value of t-account for every indicators on creative characters was bigger than t-table. Thus the hypothesis of this research that the treffinger-surrounding based method could increase the students' creative characters, can be accepted.